The Effect of Trichoderma sp Fungus on the Growth and Development of Kale Plants (Ipomoea Reptans F) - Zefanya Aqeela; Nurmahni Harahap; Halimatus Sakdiah (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Kale (Ipomoea reptans F.) is a cultivated plant that is easy to breed, has a low price, and has a has a delicious taste. However, currently, farmers and the public generally use chemical fertilizers to improve the growth and development of kale plants. This can certainly cause dependence on chemical fertilizers. So, the researchers conducted research on the effect of Trichoderma sp. The purpose is to determine the effect of Trichoderma sp. fungus on the growth and development of kale plants (Ipomoea reptans F). The method in this study is an experiment using Trichoderma sp. fungus mixed with compost with the composition of (P1) 45 gr Trichoderma sp. fungus, (P2) 50 gr Trichoderma sp. fungus, (P3) 55 gr Trichoderma sp. fungus, and (P0) without treatment as a control reference. The results showed that the P2 mixture of Trichoderma sp. fungus was the best composition. So, it can be concluded that the provision of Trichoderma sp. fungus affects the growth and development of kale plants (Ipomoea reptans F).